Pengembangan Mini Drone Berbasis ESP32 dengan Roll dan Pitch Control Menggunakan Algoritma PID - Ryzty, Elshinta (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2024)
A drone, or UAV (Unmanned Aerial Vehicle), is an aircraft that can be operated from a distance. Controlled by a pilot through remote control or having autonomy capabilities. Drones operate on the principle of the lifting power generated by the rotation of the beam-beam controlled by a rotor or electric motor. When the drones are activated, the control system will stabilize the drone using the stabilize feature. Furthermore, when the user controls the drone through a remote control device, the change in the angle of the sensor will be detected. When the x-axis on the joystick is more positive, the drone will automatically move on the negative x axis. On the contrary, if the x -axis of the joystick is more negative, the Drone automatically moves on the positive x as well for the y axis. In the implementation of PID controllers, the motor speed at the maximum moment is used for the maximum limit so that at the time of use the motor values are not excessive when responding when the error value on the sensor is at maximum. However, the result of the determination of the maximum PWM value did not work properly, because the mechanics made were not accurate so that at the first to final trial there was a difference of position at the initial determination. The PID control system applied to this drone still shows a tendency to experience movements that exceed the desired values, especially in the pitch and roll axes.